Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada UPTD Balai Kesatuan Pengelolaan Hutan Maria Donggomasa Di Bima - Irwan Irwan; Firmansyah Kusumayadi (Universitas Kristen Indonesia Toraja, 2023)
The Service Technical Implementation Unit (UPTD) of the Maria Donggomasa Forest Management Unit Center is one of the government agencies under the protection of the Environment and Forestry Service of West Nusa Tenggara Province which is located in the Bima region of West Nusa Tenggara province. The Service Technical Implementation Unit (UPTD) of the Maria Donggomasa Forest Management Unit is the implementing element for operational technical activities or technical investigation activities at the West Nusa Tenggara Provincial Forestry Service. The function and aim of establishing the KPH is to carry out forest management, outline National, Provincial, Regency/City forestry policies to be implemented, carry out forest management activities in its work area based on Determination Decree No.337/Menhut-VII/2009. The area of ​​the Maria Donggomasa Forest Management Unit (UPTD) includes the city and district of Bima which is divided into a working area of ​​9 resorts and has 96 employees consisting of 41 ASN and 55 workers.